(untitled) (University of Khartoum Engineering Journal, 2022)
Strengthening of reinforced concrete (RC) slabs using concrete overlay is one of the most popular strengthening techniqueswhich are used for slabs. Many experimental studies were carried out to understand the behaviour of strengthened one-way slabs using RC overlay. However, the main challenge remains to predict their structural capacity after strengthening. In this paper, a numerical model is developed to simulate the structural behaviour of strengthened slab using concrete overlay. The model accounts for non-linear behaviour of concrete utilising interpolation method in Eurocode 2. The model results are compared to the experiments from literature on slabs strengthened with RC overlay using three different connecting system at the contact surface between RC slabs and RC overlay. These systems are namely; friction, epoxy adhesive material, and shear keys. The model results are compared to the experimental results in terms of deflection, cracking, and slip between the slab and overlay. This comparison shows that the model is capable of capturing the behaviour of the strengthened slab. Considerable enhancement on the structural behaviour is also confirmed using this type of strengthening technique